2011
DOI: 10.1016/j.ccr.2011.07.008
|View full text |Cite
|
Sign up to set email alerts
|

A Cullin3-KLHL20 Ubiquitin Ligase-Dependent Pathway Targets PML to Potentiate HIF-1 Signaling and Prostate Cancer Progression

Abstract: Tumor hypoxia is associated with disease progression and treatment failure, but the hypoxia signaling mechanism is not fully understood. Here, we show that KLHL20, a Cullin3 (Cul3) substrate adaptor induced by HIF-1, coordinates with the actions of CDK1/2 and Pin1 to mediate hypoxia-induced PML proteasomal degradation. Furthermore, this PML destruction pathway participates in a feedback mechanism to maximize HIF-1α induction, thereby potentiating multiple tumor hypoxia responses, including metabolic reprogramm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
171
2
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 161 publications
(184 citation statements)
references
References 37 publications
10
171
2
1
Order By: Relevance
“…To identify novel PML ubiquitin ligases, we assayed PML ubiquitination in cells expressing a dominant-negative (DN) mutant of each CUL family protein. Consistent with our previous study (18), we found that CUL3-DN reduced PML ubiquitination. Interestingly, CUL4-DN elicited a similar effect ( Figure 1A).…”
Section: Identification Of Crl4supporting
confidence: 93%
See 2 more Smart Citations
“…To identify novel PML ubiquitin ligases, we assayed PML ubiquitination in cells expressing a dominant-negative (DN) mutant of each CUL family protein. Consistent with our previous study (18), we found that CUL3-DN reduced PML ubiquitination. Interestingly, CUL4-DN elicited a similar effect ( Figure 1A).…”
Section: Identification Of Crl4supporting
confidence: 93%
“…Plasmids encoding Myc-ubiquitin, His-ubiquitin, Myc-CUL3, Myc-ROC1, Flag-PML-I, and Flag-PML-IV were described previously (18). WDR4 cDNA (39) was subcloned to pRK5 with a Myc-or V5-tag, and WDR4 mutants were generated by site-directed mutagenesis.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A few ubiquitin E3 ligases have been reported to promote loss of PML under specific circumstances. For example, the KLHL20-Cul3-ROC1 complex downregulates PML in response to hypoxia (Yuan et al, 2011), and SIAH1 and SIAH2 can induce PML degradation upon overexpression (Fanelli et al, 2004). In addition, E6AP has been identified as a PML regulator in Burkitt's lymphoma (Wolyniec et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…9 Recently, it has been discovered that PML also plays a role in regulating cell migration through the transcriptional control of integrin b1 and the translational control of HIF1a. 10,11 In addition, PML plays important roles in regulating cancer stem cells. 12 Nevertheless, the role of PML in the process of lung cancer metastasis remains unclear.…”
Section: Introductionmentioning
confidence: 99%